2023
DOI: 10.1161/hypertensionaha.122.19448
|View full text |Cite
|
Sign up to set email alerts
|

Resolvin D2 Attenuates Cardiovascular Damage in Angiotensin II-Induced Hypertension

Abstract: BACKGROUND: Resolution of inflammation is orchestrated by specialized pro-resolving mediators (SPMs), and this would be impaired in some cardiovascular diseases. Among SPMs, resolvins (Rv) have beneficial effects in cardiovascular pathologies, but little is known about their effect on cardiovascular damage in hypertension. METHODS: Aorta, small mesenteric arteries, heart, and peritoneal macrophages were taken from C57BL/6J mice, infused or not with Angi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 52 publications
(91 reference statements)
1
4
0
1
Order By: Relevance
“…Left ventricular hypertrophy, characterized by cardiomyocyte hypertrophy and cardiac fibrosis, is one of the main hallmarks of hypertensive heart disease (Susic and Frohlich, 2000). Accordingly, AngII-infused mice exhibited left ventricular hypertrophy and increased cardiomyocyte area and fibrotic markers collagen I and Bnp levels, as previously described (Díaz del Campo et al, 2023). ITH13001 treatment prevented these effects, suggesting an amelioration of hypertensive heart disease; these results agree with the protective effects on cardiac remodelling of antioxidants such as Mito-TEMPO, Mitoquinone, sulforaphane, allicin and N-acetylcysteine in animal models of cardiovascular pathologies (Lombardi al., 2009;Li et al, 2012;Martínez-Revelles et al, 2013; Goh et al, 2019;Ramachandra et al, 2021;Su et al, 2021).…”
Section: Discussionsupporting
confidence: 62%
“…Left ventricular hypertrophy, characterized by cardiomyocyte hypertrophy and cardiac fibrosis, is one of the main hallmarks of hypertensive heart disease (Susic and Frohlich, 2000). Accordingly, AngII-infused mice exhibited left ventricular hypertrophy and increased cardiomyocyte area and fibrotic markers collagen I and Bnp levels, as previously described (Díaz del Campo et al, 2023). ITH13001 treatment prevented these effects, suggesting an amelioration of hypertensive heart disease; these results agree with the protective effects on cardiac remodelling of antioxidants such as Mito-TEMPO, Mitoquinone, sulforaphane, allicin and N-acetylcysteine in animal models of cardiovascular pathologies (Lombardi al., 2009;Li et al, 2012;Martínez-Revelles et al, 2013; Goh et al, 2019;Ramachandra et al, 2021;Su et al, 2021).…”
Section: Discussionsupporting
confidence: 62%
“…Previous studies have shown that there is an imbalance between proinflammatory and resolution mediators in hypertension, and low SPM levels may be an indicator of the development of hypertension [ 32 , 33 ]. Resolvin D2 has been proven to improve Ang II-induced hypertension by modulating vascular factors, fibrosis and inflammation to protect cardiovascular structure and function [ 33 ]. RvD1 also plays a cardioprotective role in angiotensin II-induced hypertension and cardiac remodeling, but the mechanism by which RvD1 improves hypertension is unclear [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular disorders, including hypertension, are associated with vascular damage, endothelium dysfunction, adventitial fibrosis, and inflammation. An interesting methodological solution was presented by the Briones research group, which studied two different groups of mice with hypertension: first, a prevention group in which angiotensin II (AngII)-infused mice were treated with RvD2 (100 ng/mouse) one day before AngII infusion and throughout the experiment (every two days); second, an intervention group in which RvD2 was given at day seven after AngII infusion till the end of the experiment [ 56 ]. They proved that administration of RvD2 to hypertensive mice prevented and reduced changes in cardiovascular function, remodelling, fibrosis, immune cell infiltration, and inflammation.…”
Section: Rvd2/gpr18 Axis In the Resolution Phase Of Inflammationmentioning
confidence: 99%